Integrasi Gaya Bekerja Hybrid dan Kepemimpinan terhadap Kepuasan Kerja dengan Moderasi Karakteristik Pekerjaan - Lusiati, Miranti; Ginting, Ginta; Pictor Siolemba, Shine (Program Studi Manajemen FEBM UMRAH, 2025)
The shift in work patterns after the pandemic has encouraged organizations to adopt more flexible systems through hybrid work arrangements. However, the effectiveness of this system remains a challenge in maintaining employee job satisfaction across industries. This study aims to analyze the influence of hybrid work style integration and leadership on job satisfaction and examine the moderating role of job characteristics in optimizing hybrid work implementation across industries in Indonesia. A quantitative approach was employed using a survey method targeting active employees who have been working under a hybrid system for at least six months. Purposive sampling was used, and data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results indicate that leadership has a positive and significant effect on both hybrid work style and job satisfaction, while hybrid work style does not significantly affect job satisfaction. Furthermore, job characteristics have a significant effect on job satisfaction but do not moderate the relationship between hybrid work style and job satisfaction. These findings highlight that adaptive leadership and meaningful job characteristics are essential factors in enhancing employee satisfaction, whereas work flexibility alone is insufficient to ensure optimal satisfaction.